BRCA2 Mutation as a Possible Cause of Poor Response to 177Lu-PSMA Therapy. (August 2018) - Ahmadzadehfar, Hojjat; Gaertner, Florian; Lossin, Philipp S.; Schwarz, Bettina; Essler, Markus
Abstract : Abstract: We present the case of a 66-year-old man with castration-resistant prostate cancer, with an increasing prostate-specific antigen level, and a progressive disease during 177 Lu-PSMA radionuclide therapy. Because the patient had a BRCA2 mutation, poly-ADP ribose polymerase inhibitor therapy was started. The patient showed a dramatic subjective and biological response to this therapy with a progression-free survival of 5 months.